Persepsi Mahasiswa Akuntansi Non-Muslim Terhadap Mata Kuliah Akuntansi Syariah di Universitas Tadulako - Yulianti, Yulianti; Muliati, Muliati; Jurana, Jurana; Halwi, Muhammad Darma; Yamin, Nina Yusnita; Mustamin, Mustamin (AKTSAR: Jurnal Akuntansi Syariah, 2022)
The research aims to determine non-Muslim accounting students' perception of Sharia accounting courses. This study examines four dimensions: knowledge, experience, methods, and motivation. The data were analyzed using a qualitative descriptive method, and the data source was obtained from interviews. This study had six informants: five non-Muslim accounting students and one accounting lecturer. The research finding shows that from the knowledge dimensions, namely knowing the transparency of sellers and buyers (murabahah contracts), a different source of income, differences in PSAK. The second dimension of experience is that non-muslim accounting students are comfortable teaching lecturers, get benefits, and positively respond to Sharia accounting. The third dimension is the learning method provided, which accounting students like the discussion method during learning. The fourth dimension is motivation to work in Islamic banks and motivated by non-Muslim lecturers who research Islamic accounting.